“My Dude, Are You Tired? I’m Tired:” An Intersectional Methodological Intervention - Spielhagen, Alexandra; Hernández, Leandra H.; Blevins, Maria (Frontiers in Communication, 2021)
This manuscript is a methodological intervention that addresses ethical considerations associated with conducting research in outdoor spaces, particularly with communities of color and other marginalized communities. The core issue is that BIPOC individuals, LGBTQIA+ individuals, and disabled individuals face discrimination and violence in outdoor/recreational spaces. By investigating these issues, scholars can intensify the problem. We hope that our perspectives can assist ethical decision-making processes in methodology, advocacy, and interaction with outdoor communities of color.